A Small Planar Antenna for 4G Mobile Phone Application. (9th May 2016) - Jian-rong, Hu; Jiu-sheng, Li; Di, Wu
Abstract : The analysis and design of a small planar multiband antenna operating in the 4G frequency bands are presented. The numerical and experimental results demonstrated that the proposed antenna satisfies the requirement of 6 dB return loss for the impedance bandwidth of the LTE700/LTE2300/LTE2500 and WiMAX3500 bands. The gains at 750 MHz/2.3 GHz/2.6 GHz/3.5 GHz are 2.1 dBi/4.9 dBi/4.7 dBi/4.3 dBi, respectively. The measured radiation patterns verify the suitability of the antenna to be employed in mobile phones. The dimensions of the radiant patch are 49 × 10 mm 2 . The proposed antenna can be easily fabricated and customized to various 4G mobile phones as a compact internal antenna.